RESTORATIVE JUSTICE CONCEPT ON JARIMAH QISHAS IN ISLAMIC CRIMINAL LAW - Zainuddin, Zainuddin (Jurnal Dinamika Hukum, 2017)
Essentially, Islamic law is modern law since it has recognized restorative justice for jarimah qishas (murder or torture). The concepts of restorative justice in Islamic criminal law realize fairness and balance to the offender and the victim themselves. Restorative justice in Islamic criminal law as explicitly provided in Q.S. al-Hujurat (49): 10 and Q.S. Asy-Syuura (42): 40. The Quran regulates peace and forgiveness in solving a crime. The existence of peace and forgiveness aims to realize the unity and sustainability of life as a purpose of the laws. Peace and forgiveness are premium remedium while the penalty is ultimun remediun in Islamic criminal law. Otherwise, in modern criminal law, the penalty is premium remedium.Keywords: Forgiveness, Peace, Qishas, Restorative Justice